1969
DOI: 10.2307/4593531
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders among the Patients of General Practitioners and Internists

Abstract: ABOUT 10 to 60 percent of the people receiving care from a general practitioner or interniist during a year have a significant emotional or psychiatric problem-as perceived by the physician. But how perceptive is the average family physician in detecting mental illness, and what factors influence his perceptiveness? If the family physician is to function as a resource for early detection of mental illness, how must his training be altered? And how would the caseload for all the psychiatric services in a commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Prior studies have suggested that primary care medical practitioners diagnose the existence of mental illness in 2% to 16% of their patients (Shepherd et al, 1966;Hoeper et al, 1979;Eastwood, 1971;Patrick et al, 1978;Hankin et al, 1982;Locke and Gardner, 1969). Prevalence rates for diagnosable mental disorders in primary care patients range from 15% to 40% (Shepherd et al, 1966;Hoeper, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that primary care medical practitioners diagnose the existence of mental illness in 2% to 16% of their patients (Shepherd et al, 1966;Hoeper et al, 1979;Eastwood, 1971;Patrick et al, 1978;Hankin et al, 1982;Locke and Gardner, 1969). Prevalence rates for diagnosable mental disorders in primary care patients range from 15% to 40% (Shepherd et al, 1966;Hoeper, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the family physician is particularly pivotal in this instance because he appears early in the career of the emotionally disturbed patient and is frequently the first professional consulted. 23 In sanctioning secondary deviance as genuine illness, the family physician may unwittingly confirm the symptomatic life style of many "labeled" patients. Until we improve our evaluational techniques to distinguish between legitimate and labeled symptomatology, it is possible that primary physicians are actually "sending on" as many patients as they deter from careers of symptomatic emotional illness.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of these patients was 44 years and the majority were married (65 per cent). The distribution by social class was I-II, 23 Index.' 9 …”
Section: Methods Samplementioning
confidence: 99%
“…1,2 Patients with psychiatric problems typically come to the doctor with physical complaints.3'4 Nonetheless, it is known that physical complaints may be secondary to an underlying mental problem, and if the mental problem is recognized and successfully treated, the physical problems may be alleviated as well. 3,4 This pilot study was designed to investigate the extent and nature of mental disorders among those patients claiming physical disability.…”
Section: Introductionmentioning
confidence: 99%